An approach to implement interactive teaching in blended learning environments - Sayed, Mohamed (Journal of Advanced Computer Science & Technology, 2015)
The use of electronic response systems in classrooms can be effective, especially when coupled with a method allowing a question to be broken into manageable interactive questions. This paper develops the use of electronic response systems as a part of leading assessment delivery and data collection solutions in a blended learning environment. The technology that is the subject of this research consists of thirty-button response cards that transmit student responses to a receiver connected to the instructor laptop. The electronic response systems are proven to enhance the effective instructions, increase retentions, engage participants, and immediately assess understanding.